Learning attitude, ethics, and communication: Perspectives from first year medical students - A cross-sectional study - Mrunal R. Shenwai; Priya Mardikar (Al Ameen Journal of Medical Sciences)
Objectives: Medical education traditionally emphasized on cognitive and psychomotor domains, often overlooking the affective domain. However, the National Medical Commission (NMC) now stresses the importance of training in Attitude, Ethics, and Communication (AETCOM). This study aimed to evaluate first-year MBBS students' perspectives on the AETCOM teaching-learning experience. Methods: A cross-sectional study was conducted in the Department of Physiology, SKNMC & GH, Pune, Maharashtra, involving 150 first-year MBBS students from the 2019-20 batch. The AETCOM Module 1.2 was delivered over a month through exploratory sessions, hospital visits, self-directed learning (SDL), and discussion sessions. Feedback was collected from 109 students via a Likert scale-based questionnaire administered through Google Forms. Results: The feedback revealed that 73.9% of students rated the exploratory session as excellent. 75.9% strongly agreed that hospital visits improved their understanding of patient experiences. 99.1% felt sensitized to patients' rights and 98.1% gained insights from peers' experiences. 93.6% found movie clips very effective and all 100% felt that the faculty role plays were helpful. 98.2% felt the hospital visits were smoothly facilitated & 97.3% appreciated the SDL sessions. Conclusion: Students responded positively to the AETCOM module. The use of innovative teaching methods enhanced their understanding, with recommendations for continued guidance in reflective writing.